Silica Filter Membrane by Utilizing Palm Oil Empty Bunches Waste - Reco Rambang Putra Negsagis; Hari Firmansah; Ultra Marsedi (Jurnal Indonesia Sosial Sains, 2024)
Keramasan Gas and Steam Power Plant uses river water as raw material after going through treatment in the WTP system. To overcome the problem of high silica value in demin water, a ceramic filter membrane device was developed from empty palm oil bunch waste that reduced silica content to standards. This research aims to improve water treatment efficiency to meet the established water quality standards. Keramasan Gas and Steam Power Plant uses river water sources as raw materials, which are processed through the WTP (Water Treatment Plant) system to produce demineralized water as the main supply in the HRSG water filler system. However, the water treatment process has not been optimal because the silica content in demin water is still high (>20 PPB), violating the established quality standards (<20 PPB). Therefore, this study proposes an innovation in the form of a ceramic filter membrane from empty palm oil bunch waste to reduce silica content. Tests show a decrease in silica values to standard. These innovations have had a positive impact, including chemical savings, water treatment optimisation, and wastewater reduction. In addition, the use of empty palm oil waste also contributes to efforts to reduce environmental pollution.